HPV Induces Changes in Innate Immune and Adhesion Molecule Markers in Cervical Mucosa With Potential Impact on HIV Infection - Britto, Alan Messala A.; Goes, Livia R.; Sivro, Aida; Policarpo, Cintia; Meirelles, Ângela R.; Furtado, Yara; Almeida, Gutemberg; Arthos, James; Cicala, Claudia; Soares, Marcelo A.; Machado, Elizabeth S.; Giannini, Ana Lúcia M. (Frontiers in Immunology, 2020)
While most HPV infections are asymptomatic and clear spontaneously, persistent infection with high-risk HPVs is associated with cervical cancer and with increased risk of HIV acquisition. Although several hypotheses have been proposed to explain this phenomenon, none has been confirmed. Our aim was to investigate the expression of host factors involved in the susceptibility to HIV infection among HPV-infected women. Cervical samples were collected to characterize the expression levels of HIV susceptibility markers in the mucosa of HPV-infected compared with HPV-uninfected women. No differences in the frequency of CCR5+, integrin α4β7+, activated and memory CD4+ T-cell were detected between the groups. We additionally evaluated the expression levels of genes involved in innate immune responses and in cell adhesion. HPV infected patients expressed higher levels of TLR9 and lower levels of pattern recognition receptors that recognize RNA (TLR3, TLR7, and MDA5/IFIH1). We also detected an impaired IFN pathway, with an increased Type I IFN and a decreased IFNα2 receptor expression. HPV+ samples displayed reduced expression of genes for adherens and tight junctions. Taken together, these results suggest that although HPV infection does not result in the recruitment/activation of susceptible CD4+ T-cell in the female genital tract, it leads to changes in the innate antiviral immune responses and in cell adhesion that are likely to favor HIV infection.